What motivates academics toward entrepreneurship? Examining the formation of academic entrepreneurial intention from the push-pull perspective - Yu, Zhaoyuan; Lu, Kangyin (Frontiers in Psychology, 2023)
Introduction Although academic entrepreneurship has received considerable attention over the last decades, little attention has been devoted to discussing the formation process of academic entrepreneurial intention underlying the push-pull perspective. This study attempts to explore the mechanism of how academic entrepreneurial intention is shaped, with job-related negative elements as push factors, and entrepreneurship-related positive attractors as pull factors. Methods In this paper, regression analysis and Bootstrap were conducted using SPSS 26.0 and MPLUS 7.0, whose applicability has been widely demonstrated in research. Results Findings were derived from 1042 academics from Chinese universities. Results showed that both push and pull factors do contribute to boosting academic entrepreneurial intention. Particularly, the entrepreneurship-related pull factors including entrepreneurial opportunity identification and expected entrepreneurial benefits play a dominant role in trigging academic intention to engaging entrepreneurship. Moreover, our findings further confirmed the moderating role of social network in the process of academics pushed by negative job-related factors to emerge entrepreneurial intention. Discussion This study extends the research perspective on the factors influencing academic entrepreneurial intention by examines the impact of push and pull factors on academic entrepreneurial intention simultaneously. This deepens the formation mechanism of academic entrepreneurial intention. Besides, the current study identifies a new look at the role that social network plays in academic entrepreneurship.